PENGARUH MIKORIZA DAN PUPUK NPK TERHADAP KETERSEDIAAN DAN SERAPAN NPK PADA TANAMAN JAGUNG - Charly Mutiara (Agriculture - Jurnal Ilmu Pertanian, 2022)
Research was carried out to determine the effect of mycorrhizal doses and NPK fertilizer on the availability and uptake of NPK in corn plants. The research results showed that mycorrhizal inoculation and NPK fertilizer doses were able to increase the availability of soil NPK, plant tissue NPK, plant dry weight, and dry shelled seed weight. In the mycorrhizal and NPK inoculation treatment for all these variables, it showed an increase in all variables; however, mycorrhizal inoculation and NPK at a dose of 75% for each variable value decreased. The influence factors of mycorrhiza and NPK significantly increased these variables when compared to those without mycorrhiza and NPK fertilizer. The optimum dose of mycorrhizal inoculation fertilizer (m1, m2 and m3) and the dose of NPK fertilizer are each found at a fertilizer dose of 50.66% of the recommended NPK fertilizer (75.99 kg-1 ha urea, 25.33 kg ha-1 SP- 36 and KCl) or equivalent to 0.38 g/polybag urea and 0.31 g/polybag SP-36 and KCl), 45.11% of the recommended NPK fertilizer (67.66 kg ha-1 urea, 22.55 kg ha-1 SP-36 and KCl) or the equivalent of 0.34 g/polybag urea and 0.28 g/polybag SP- 36 and KCl, and 46.10% of the recommended NPK fertilizer (69.15 kg ha-1 urea and 23.05 SP-36 kg ha-1 and KCl) or equivalent to 0.34 g/polybag urea and 0.28 g/polybag SP-36 and KCl. The results of the optimum dose achieved in the combination treatment of mycorrhiza and NPK turned out to show the lowest optimum dose in the indigenous mycorrhiza treatment when compared to exogenous mycorrhiza. In the treatment without mycorrhiza (m0), there was a linear effect, namely, there was no optimum dose. Corn plants that are not given mycorrhiza require fertilizer at a dose exceeding 100% of the fertilizer dose given to reach the optimum dose.